COVID-19 and kidney - M. Kolesnyk (Український Журнал Нефрології та Діалізу, 2020)
At the beginning of COVID-19 pandemic attention of healthcare professionals and scientists were already drawn to the appearance of markers of pathologic changes of the urinary system in SARS-CoV-2-infected patients, signs of acute kidney disease (AKD) (including acute kidney injury (AKI) or development of AKI in patients with chronic kidney disease (CKD). This necessitates verification of pathologic changes markers of the urinary system in SARS-CoV-2-infected patients and clarification of their nosologic relevance.